Improvement of Visible‐Light H2 Evolution Activity of Pb2Ti2O5.4F1.2 Photocatalyst by Coloading of Rh and Pd Cocatalysts. Issue 43 (16th June 2022) - Aihara, Kenta; Kato, Kosaku; Uchiyama, Tomoki; Yasuda, Shuhei; Yokoi, Toshiyuki; Yamakata, Akira; Uchimoto, Yoshiharu; Maeda, Kazuhiko
Abstract: Pb2 Ti2 O5.4 F1.2 modified with various metal cocatalysts was studied as a photocatalyst for visible‐light H2 evolution. Although unmodified Pb2 Ti2 O5.4 F1.2 showed negligible activity, modification of its surface with Rh led to the best observed promotional effect among the Pb2 Ti2 O5.4 F1.2 samples modified with a single metal cocatalyst. The H2 evolution activity was further enhanced by coloading with Pd; the Rh−Pd/Pb2 Ti2 O5.4 F1.2 photocatalyst showed 3.2 times greater activity than the previously reported Pt/Pb2 Ti2 O5.4 F1.2 . X‐ray absorption fine‐structure spectroscopy, photoelectrochemical, and transient absorption spectroscopy measurements indicated that the coloaded Rh and Pd species, which were partially alloyed on the Pb2 Ti2 O5.4 F1.2 surface, improved the electron‐capturing ability, thereby explaining the high activity of the coloaded Rh−Pd/Pb2 Ti2 O5.4 F1.2 catalyst toward H2 evolution. Abstract : Visible‐light‐induced H2 evolution activity of a Pb2 Ti2 O5.4 F1.2 photocatalyst was found to be sensitive to the loaded metal cocatalyst. Although Rh was the most effective single‐metal cocatalyst among the tested metals, the activity of Rh/Pb2 Ti2 O5.4 F1.2 was further improved by coloading of Pd because it reinforced the ability of Rh to capture photogenerated electrons from Pb2 Ti2 O5.4 F1.2 .